Georgia Competitive Industries Preliminary Sector Diagnostic - Onugha, Ifeyinwa; Iootty, Mariana; Kilroy, Austin; Palmade, Vincent (World Bank, Washington, DC, 2013)
As a small and open economy, Georgia's growth prospects are directly linked to its ability to produce and sell goods and services competitively in the global marketplace. The World Bank Georgia Competitive Industries Technical Assistance Project has been launched in February 2013 in response to the December 19, 2012 letter of the Ministry of economy and sustainable development of Georgia with the request to get the Bank's support in diagnoses of trade competitiveness and identification of a road map for reform to enhance Georgia's export growth and competitiveness. The project is envisioned as a three phase program, that comprises: February-June 2013 analytical and technical assistance support, including diagnostic of trade competitiveness and constraints to export growth, and competitive industries sector diagnostic report, supported by extensive discussions through a series of workshops, private and public sector interviews, discussions and a large 2-day seminar on February 28-March 1, 2013; July-December 2013-deep dive analysis of selected competitive industries and development of a reform road map to support Georgia's competiveness strategy; and from January 2013-reform implementation, supported by the Bank's technical assistance, policy advice and lending operations. The report is prepared on the basis of the competitive industries sector prioritisation framework. The report incorporates ideas and recommendations received during February 28-March 1, 2013 seminar and several smaller workshops and brainstorming sessions held in March-May 2013. Export led growth provides also a strong motivation to reform the domestic industries which will continue to account for the vast majority of employment. Georgia's main domestic industries include agriculture, retail/wholesale, construction, transportation, health and education. Since economic growth is accounted for by productivity improvements by workers in all industries, export-led growth can play a key role in raising these productivity levels.